2023
DOI: 10.3390/ijerph20054499
|View full text |Cite
|
Sign up to set email alerts
|

A Current Review of Water Pollutants in American Continent: Trends and Perspectives in Detection, Health Risks, and Treatment Technologies

Abstract: Currently, water pollution represents a serious environmental threat, causing an impact not only to fauna and flora but also to human health. Among these pollutants, inorganic and organic pollutants are predominantly important representing high toxicity and persistence and being difficult to treat using current methodologies. For this reason, several research groups are searching for strategies to detect and remedy contaminated water bodies and effluents. Due to the above, a current review of the state of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 132 publications
0
8
0
Order By: Relevance
“…Through various pathways, CECs contaminate soil, water, and air, affecting the environment and human health (Figure 1) [141]. A variety of analytical techniques have been employed to detect and quantify inorganic and organic contaminants in aqueous matrices; however, the presence of contaminants in water has demonstrated that current quality controls cannot detect or treat pollutants that are present [142]. Nevertheless, detection techniques still include chromatographic, spectroscopic, electrochemical, and colorimetric titration amongst others.…”
Section: Management Detection and Possible Treatment Of Cec Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Through various pathways, CECs contaminate soil, water, and air, affecting the environment and human health (Figure 1) [141]. A variety of analytical techniques have been employed to detect and quantify inorganic and organic contaminants in aqueous matrices; however, the presence of contaminants in water has demonstrated that current quality controls cannot detect or treat pollutants that are present [142]. Nevertheless, detection techniques still include chromatographic, spectroscopic, electrochemical, and colorimetric titration amongst others.…”
Section: Management Detection and Possible Treatment Of Cec Exposuresmentioning
confidence: 99%
“…Nevertheless, detection techniques still include chromatographic, spectroscopic, electrochemical, and colorimetric titration amongst others. Each of these methods weigh in with various advantages and disadvantages as critically discussed by Warren-Vega et al [142].…”
Section: Management Detection and Possible Treatment Of Cec Exposuresmentioning
confidence: 99%
“…The most common anthropogenic pollutants of surface waters include pesticides, surfactants, petroleum hydrocarbons, phenols, chlorinated biphenyl derivatives, dyes, polymeric substances (including proteins) and heavy metals: lead, copper, chromium, cadmium, mercury and zinc, [17] as well as heated waters (thermal pollution), which are particularly dangerous for surface reservoirs with low flow or stagnant waters [18] . Such a complex composition of wastewater, which is constantly changing due to the introduction of newly developed substances (e. g. drugs or plant protection products), requires the constant development of novel carbon adsorbents that would allow for the effective separation of as many components as possible at the same time [19,20] …”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of industry, medicinal compounds are a new kind of pollutants, which pose a serious threat to water resources. [ 1 ] The pharmaceutical compounds are usually complex in structure and have poor biodegradability, so they are difficult to be removed from the influent water. [ 2 ] It is reported that Ofloxacin (OFX) is one of the most widely used antibiotics in poultry and aquaculture in the world, and its extensive use poses a great threat to the environment.…”
Section: Introductionmentioning
confidence: 99%